2020
DOI: 10.3390/su12166325
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Default Predictions Using Machine Learning: Literature Review

Abstract: Corporate default predictions play an essential role in each sector of the economy, as highlighted by the global financial crisis and the increase in credit risk. This study reviews the corporate default prediction literature from the perspectives of financial engineering and machine learning. We define three generations of statistical models: discriminant analyses, binary response models, and hazard models. In addition, we introduce three representative machine learning methodologies: support vector machines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Single-label and multi-label classifiers are tested in [20], demonstrating that multilabel classifiers perform better. In addition, the ML methods furnish a better fit for the nonlinear relations between the default risk and explanatory variables [21]. See also [22] for further discussions.…”
Section: Introductionmentioning
confidence: 99%
“…Single-label and multi-label classifiers are tested in [20], demonstrating that multilabel classifiers perform better. In addition, the ML methods furnish a better fit for the nonlinear relations between the default risk and explanatory variables [21]. See also [22] for further discussions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most famous machine learning techniques is the artificial neural network, which is very useful when it comes to solving complex and non-linear relationships "by mimicking the structure of the brain and connecting artificial neurons using simple structures" (Kim et al, 2020). Machine learning techniques have been used in default predictions before the 1990s, and several authors (Yang et al, 1999;Zhao et al, 2014;Geng et al, 2015;Jones et al, 2017) have demonstrated that they have both better prediction performances than Logit/probit and, on average, good levels of efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A significant strand of literature has found that intelligent models in credit default prediction models are efficient in predicting corporate defaulting [20,[26][27][28]. Without the strict assumptions of the traditional statistical models (e.g., independence and normality among predictor variables), intelligent techniques can automatically derive knowledge from training data [28][29][30].…”
Section: Credit Default Prediction Modelsmentioning
confidence: 99%